Interventions to improve antiretroviral adherence in HIV-infected pregnant women: A systematic review and meta-analysis - Zhou, Jie; Yun, Jingyi; Ye, Xinxin; Liu, Wen; Xiao, Wenhan; Song, Peige; Wang, Hongmei (Frontiers in Public Health, 2022)
Background Medication adherence in HIV-infected pregnant women remains suboptimal. This systematic review and meta-analysis aimed to evaluate the effectiveness of interventions on improving antiretroviral adherence targeting among HIV-infected pregnant women. Methods Five databases were screened to identify quasi-experimental studies and randomized controlled trials. The risk ratios (RR) and confidential intervals (CI) were extracted to estimate the improvement in antiretroviral adherence after interventions compared with control conditions. This study was registered with PROSPERO, number CRD42021256317. Results Nine studies were included in the review, totaling 2,900 participants. Three interventions had significance: enhanced standard of care (eSOC, RR 1.14, 95%CI 1.07–1.22, Z = 3.79, P < 0.01), eSOC with supporter (RR 1.12, 95%CI 1.04–1.20, Z = 2.97, P < 0.01) and device reminder (RR 1.33, 95%CI 1.04–1.72, Z = 2.23, P = 0.03). Discussion The study supported the eSOC and the device reminder as effective intervention strategies for improving HIV medication adherence. Based on the current findings, the study called for more efforts to improve antiretroviral care for pregnant women through involving multicenter, large-sample, and high-quality research and combining the device reminder with other intervention methods. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021256317, identifier CRD42021256317.